2015
DOI: 10.1111/jpn.12295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing rare earth element cerium on rumen fermentation, nutrient digestibility, nitrogen balance and plasma biochemical parameters in beef cattle

Abstract: The objectives of the trial were to investigate the effects of supplementing rare earth element (REE) cerium (Ce) on rumen fermentation, nutrient digestibility, methane (CH4 ) production, nitrogen (N) balance and plasma biochemical parameters in beef cattle. Four Simmental male cattle, aged at 14 months, with initial liveweight of 355 ± 8 kg and fitted with permanent rumen cannulas, were used as experimental animals. The cattle were fed with a total mixed ration (TMR) composed of concentrate mixture and corn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…On day 15 of each period, a mobile open‐circuit respirometry system described by Lin et al. () was used to take gas samples exhaled from each cattle. The respirometry system was consisted of a face mask connected to two corrugated PVC tubes and a Tedlar bag with a maximum of 500 l (Safelab Technology Co. Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…On day 15 of each period, a mobile open‐circuit respirometry system described by Lin et al. () was used to take gas samples exhaled from each cattle. The respirometry system was consisted of a face mask connected to two corrugated PVC tubes and a Tedlar bag with a maximum of 500 l (Safelab Technology Co. Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Schwabe et al (2011Schwabe et al ( , 2012 supplemented German Holstein bulls with REE citrate (100-300 mg/kg) finding decreased weight gain, but accumulation in liver, kidneys, and rib bone with increasing REE supplementation. Three studies were conducted on ruminally cannulated steers and found improved rumen fermentation and increased digestibility of neutral detergent fiber (Liu et al 2008;Xun et al 2014;Lin et al 2015).…”
Section: Rees As Feed Additives In Livestockmentioning
confidence: 99%
“…REE-associated effects in plant models ranged from growth stimulation (hormesis) to inhibitory effects as a function of REE concentration (Poschenrieder 2013;Morkunas et al 2018;Nascarella and Calabrese 2016;Liu et al 2016a, b;Xu et al 2002); 2. Different accumulation gradients were noted in plant and animal organs, with minimal-if any-accumulation in the edible parts (Xu et al 2002;Tariq et al 2020); Liu et al (2008) Ruminally cannulated Simmental steers CeCl 3 80-240 Increased the digestibility of neutral detergent fibre, decreased molar ratio of rumen acetate to propionate Lin et al (2015) 3. REE-based feed additives in poultry failed to result in increased weight gain in broiler chicks, whereas REEsupplemented laying hens improved quantitative and qualitative egg production (Durmuş and Bölükbaşı 2015;Bölükbaşı et al 2016;Cai et al 2016); 4.…”
Section: Ree-associated Uses In Agriculture and Zootechny: State-of-tmentioning
confidence: 99%
“…We reviewed 34 published studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] that were obtained by searching within the Web of Science platform using ‘purine derivatives’ and ‘beef cattle’ as keywords for the document search. We only included studies that reported results for UPD excretion alongside recording feed dry matter (DM) intake, animal weight, and dietary components (CP and neutral detergent fibre (NDF) on a DM basis).…”
Section: Analysis Of Factors Affecting Urinary Purine Derivative Excr...mentioning
confidence: 99%